Higher-resolution wavefront sensing based on sub-wavefront information extraction - Guan, Hongli; Zhao, Wang; Wang, Shuai; Yang, Kangjian; Zhao, Mengmeng; Liu, Shenghu; Guo, Han; Yang, Ping (Frontiers in Physics, 2024)
The limited spatial sampling rates of conventional Shack-Hartmann wavefront sensor is unable to sense higher-order wavefront distortion. In this study, by etching a known phase on each microlens to modulate sub-wavefront, we propose a higher-resolution wavefront reconstruction method that employs a modified modal Zernike wavefront reconstruction algorithm, of which the reconstruction matrix contains quadratic information that is extracted by a neural network. We validate this method through simulation, results show that, once the network has been trained, for various atmosphere conditions and spatial sampling rates, the proposed method enables fast and accurate high-resolution wavefront reconstruction. Furthermore, it has highly competitive advantages such as fast dataset generation, simple network structure, and short prediction time.